Psychosocial Effect of COVID-19 Phobia in Health Workers in the Pandemic Service and Intensive Care - Merve Bülbül; Ayşe Nur İnci Kenar; Gonca Ayşe Ünal (Genel Tıp Dergisi)
Objective: It was aimed to evaluate the phobia levels of COVID-19 (Coronavirus disease 2019) in medical staff working in the pandemic service and intensive care service and to examine its relationship with psychosocial impact levels. Material and Method: The study included 100 people working in the pandemic service and intensive care units in the first year of the pandemic. Sociodemographic Data Form, COVID-19 Pandemic Psychosocial Impact Scale (CPPIS) and COVID-19 Phobia Scale (CPS) were administered to all participants. Results: The mean age of the participants was 32.5±7.4 years and 74% of them were women. Of them 29% were doctors, 52% were nurses, 19% were allied health personnel and 66% worked in the service, 29% in the intensive care unit and 5% in both. There were very strong correlations between the CPS and the CPPIS total score, the death anxiety and anxious thoughts subscale scores. A strong positive correlation was found between the CPS and CPPIS subscales scores including close relationships, functionality and somatic symptoms. A significant positive correlation was found between CPS and CPPIS scores and the duration of working in the pandemic service and intensive care unit. Conclusion: It was thought that as choranophobia increased in medical staffs working in the pandemic service, their psychosocial effects also increased. It has been thought that reducing the working time in the service and/or intensive care unit during the pandemic, performing short-term rotations, may reduce the level of psychosocial impact and even be protective in terms of mental health of medical staff.